Some physical properties of Si₁₋xGex solid solutions using pseudo-alloy atom model - Jivani, A.R.; Trivedi, H.J.; Gajjar, P.N.; Jani, A.R. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2005)
Some electronic, thermodynamical and mechanical properties of Si1-xGex solid solution with an arbitrary (atomic) concentration (x) are studied using the pseudo-alloy atom model. This work is based on the pseudopotential theory of covalent crystals and on the higher-order perturbation scheme with the application of our proposed model potential. We have used the latest local field correction function proposed by Sarkar et al. alongwith other four local-field correction functions of Hartree, Taylor, Utsumi et al. and Farid et al. to study Si-Ge system. The total energy of the Si1-xGex solid solutions is investigated and compared with available experimental data. The calculated numerical values of the heat of solution for Si-Ge system are small and positive. The positive sign of the heat of solution predicts that, at low temperatures, the phase mixture will be more stable than the disordered solid solution. Like the case of simple metals, it is seen that a graph of the ratio of the heat of formations and x(1−x) against x is linear. The bulk modulus of Si1-xGex is also investigated with different concentrations x of Ge. We have found in the present study that the bulk modulus decreases linearly with an increase in the concentration x.